Optimalisasi Pengelolaan Lahan dalam Meningkatkan Produksi Jagung, Sebagai Upaya Peningkatan Pendapatan Petani Desa Bojongsana Kabupaten Tegal - Sari Wiyanti (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
The study was conducted in Bojongsana village, Suradadi Subdistrict, Tegal Regency from April to August 2018 to optimize land in increasing corn production, as an effort to increase the income of farmers in Bojongsana village, Tegal Regency. The population in this study were corn growers. The data used in this study are primary data obtained through direct interviews with respondents. While secondary data was obtained from the office of the Bojongsana Village Chief and the Suradadi Agriculture Service Office in Tegal Regency. Sampling using Purposive sampling, namely samples are farmers who have the ability and experience in planting corn according to the purpose of this study. Data and information collected then processed and discussed qualitatively descriptive. The results show that by optimizing the land after the rice harvest, which is utilized for corn production with the strategy of the SWOT analysis can increase farmers' income. To meet market demand for corn, there needs to be a sustainable development of corn production in Bojongsana village, Suradadi District, Tegal Regency.